Chosen through Sanctification (1 Pet 1,2 and 2 Thess 2,13). The Theology or Diction of Silvanus? - Sargent, Benjamin (2013)
This short study re-examines the theory, dominant for much of the 20th Century, that Silvanus acted as an amanuensis in the composition of 1 Peter. The phrase e(n a(giasmw=| pneu/matoj appears only in 1 Pet 1,2 and 2 Thess 2,13 in the New Testament, both of which have a stated association with Silvanus. In addition to this, the phrase is theologically incongruous, bearing no clear relation to the broader theology of either epistle.
Keywords: 1 Peter 1,2; 2 Thessalonians 2,13; Silvanus